Inhibition of miR-141-3p attenuates apoptosis of neural stem cells via targeting PBX1 to regulate PROK2 transcription in MCAO mice. Issue 4 (16th February 2023) - Liu, Tingting; Feng, Jinzhou; Sun, Zhenjie; He, Mingli; Sun, Linlin; Dong, Shuangshuang; Guo, Zhenwei; Zhang, Guanghui
ABSTRACT: MicroRNA-141-3p (miR-141-3p) has been found to be altered in the brain following a stroke. Herein, we investigate the impact of miR-141-3p on the apoptosis of neural stem cells (NSCs) in mice with middle cerebral artery occlusion (MCAO) and the potential mechanisms involved. Eight-week-old mice were injected intracerebroventricularly with miR-141-3p, antagomir-141-3p, or agomir negative control 2 h before MCAO, and animal behavior tests and infraction volume measurements were performed 24 h later. MCAO-mediated brain injury and NSCs apoptosis were observed by H&E, TTC, and TUNEL staining. The expression of cleaved caspase-3 and Ki67 was detected by western blotting. The luciferase reporter assay proved that miR-141-3p in combination with its target gene PBX homeobox 1 (PBX1). Exogenous miR-141-3p (agomir-141-3p) treatment increased infraction volume and brain edema and damaged neurological functions compared to control mice. Agomir-141-3p increased miR-141-3p expression in brain tissue of mice with MCAO and suppressed PBX1 expression. The effects of the agomir-141-3p-induced apoptosis in NSCs treated with oxygen–glucose deprivation (OGD)/reoxygenation (R) were abolished by PBX1 overexpression. The results from UCSC and JASPAR database showed that prokineticin 2 (PROK2) was a transcription factor of PBX1. The expression of PROK2 was transcriptionally regulated by PBX1 using RT-PCR and western blot assays. The effects of the apoptosis-promoting caused by PBX1 inhibition in NSCs treated with OGD/R were reversed by PROK2 inhibition. In conclusion, the miR-141-3p/PBX1/PROK2 axis might be a novel therapeutic target for the apoptosis of NSCs in MCAO.